2018
DOI: 10.1371/journal.pone.0200049
|View full text |Cite
|
Sign up to set email alerts
|

Variation and diversification of the microbiome of Schlechtendalia chinensis on two alternate host plants

Abstract: Schlechtendalia chinensis, a gall-inducing aphid, has two host plants in its life cycle. Its wintering host is a moss (typically Plagiomnium maximoviczii) and its main host is Rhus chinensis (Sumac), on which it forms galls during the summer. This study investigated bacteria associated with S. chinensis living on the two different host plants by sequencing 16S rRNAs. A total of 183 Operational Taxonomic Units (OTUs) from 50 genera were identified from aphids living on moss, whereas 182 OTUs from 49 genera were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…While insect species was the strongest driver of structure and diversity of bacterial communities in this study, diet also showed a significative effect. Several previous studies showed that insect-associated microbial communities are often shaped by their host's diet, for example in termites (Mikaelyan et al, 2015), aphids (Wu et al, 2018;Xu et al, 2019Xu et al, , 2020Holt et al, 2020), bugs (Martinez et al, 2019), beetles (Kim et al, 2017), fruit flies (Malacrinò et al, 2018;Majumder et al, 2019;Woruba et al, 2019;Asimakis et al, 2019), soldier flies (Bruno et al, 2019) and ants (Russell et al, 2009). Interestingly, the bacterial communities associated with Phtorimaea operculella varied even according to the plant tissue insects were feeding on (Zheng et al, 2020).…”
Section: Response Of Bacterial Clades To Factors Influencing Insect Microbial Communitiesmentioning
confidence: 99%
“…While insect species was the strongest driver of structure and diversity of bacterial communities in this study, diet also showed a significative effect. Several previous studies showed that insect-associated microbial communities are often shaped by their host's diet, for example in termites (Mikaelyan et al, 2015), aphids (Wu et al, 2018;Xu et al, 2019Xu et al, , 2020Holt et al, 2020), bugs (Martinez et al, 2019), beetles (Kim et al, 2017), fruit flies (Malacrinò et al, 2018;Majumder et al, 2019;Woruba et al, 2019;Asimakis et al, 2019), soldier flies (Bruno et al, 2019) and ants (Russell et al, 2009). Interestingly, the bacterial communities associated with Phtorimaea operculella varied even according to the plant tissue insects were feeding on (Zheng et al, 2020).…”
Section: Response Of Bacterial Clades To Factors Influencing Insect Microbial Communitiesmentioning
confidence: 99%
“…The molecular mechanism of this selected gene regulation in galls remains to be determined. Moreover, 99% of S. chinensis symbiotic bacteria are Buchnera spp., the main contributors of amino acids for aphids [ 31 ]. We suppose the enhanced biosynthesis pathways of essential amino acids compensate for the lack of amino acids synthesized by Buchnera spp.…”
Section: Discussionmentioning
confidence: 99%
“…and Pseudomonas sp. are predominant in D. kuriphilus and widely distributed in galling insects, including D. kuriphilus, gall midges, gall aphids, gall sawflies and thrips [17,18,[23][24][25][26][27]63,64]. Many species of the Serratia and Pseudomonas genera are plant pathogenic bacteria [65].…”
Section: Predominant Bacteria Associated With D Kuriphilusmentioning
confidence: 99%
“…of Leptocybe invasa can resist the secondary metabolites of plants and expand the range of host feeding, which is beneficial for the colonization of L. invasa [16,17]. Buchnera aphidicola synthesizes essential amino acids for gall aphids and facilitates the stress tolerance and reproduction of the host [18,19]. Furthermore, Wolbachia may cause the parthenogenesis of some galling insects [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation